Teachers’ Perceptions of Using FluentU as Learning Media to Improve Students’ Pronunciation - Alvindi Alvindi; Yani Lubis (Tell-us Journal)
This study explores teachers' perceptions of using FluentU, a video-based language learning application, to enhance students' pronunciation skills in English as a Foreign Language (EFL) classrooms. Recognizing that pronunciation plays a crucial role in communicative competence; the research addresses the gap in studies focusing specifically on digital platforms like FluentU. The study used a qualitative phenomenological design to gather data from eight secondary school teachers in Medan through closed-ended questionnaires and semi-structured interviews. The findings reveal that teachers generally hold positive perceptions of FluentU, with an average score of 31.65 and a percentage score of 79.125%, categorizing the effectiveness of application as "Good." Teachers noted FluentU's strengths in enhancing student motivation, suprasegmental pronunciation (intonation, rhythm), and phoneme recognition. However, they expressed reservations about using FluentU as the primary tool for pronunciation instruction, citing the need for more interactive feedback and advanced segmental practice. The study concludes that while FluentU is a valuable supplementary resource for improving pronunciation, a blended learning approach may be optimal. These insights contribute to the growing field of digital-assisted language learning, highlighting the potential of interactive multimedia tools in EFL pronunciation teaching.